Weight loss before total joint arthroplasty using a remote dietitian and mobile app: study protocol for a multicenter randomized, controlled trial - Michael W. Seward; Brielle J. Antonelli; Nancy Giunta; Richard Iorio; Wolfgang Fitz; Jeffrey K. Lange; Vivek M. Shah; Antonia F. Chen (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background The months prior to elective surgery may present an opportunity for patients to initiate behavior changes that will simultaneously ready them for surgery and improve their overall health status. An upcoming elective total joint arthroplasty (TJA) may serve as motivation for patients with severe obesity (body mass index [BMI]> 40 kg/m2) to lose weight, as it may optimize clinical outcomes following TJA and help them become eligible for TJA since some surgeons use a BMI of 40 kg/m2 as a cut-off for offering surgery in an effort to optimize outcomes. Methods The purpose of this multicenter randomized, controlled trial is to assess the feasibility and efficacy of a 12-week remote dietitian (RD) supervised dietary and physical activity weight loss intervention and mobile app for 60 patients with severe obesity prior to undergoing TJA. Intervention participants will receive access to a smartphone app and connect with an RD who will contact these participants weekly or bi-weekly via video calls for up to nine video calls. Together, participants and RDs will set goals for lifestyle modifications, and RDs will check on progress towards achieving these goals using in-app tools such as food logs and text messages between video calls. All patients will be encouraged to lose at least 20 pounds with a goal BMI < 40 kg/m2 after 12 weeks. Individuals randomized to the control group will receive clinical standard of care, such as nutritionist and/or physical therapy referrals. Outcome and demographic data will be collected from blood serology, chart review, mobile app user data, pre- and postintervention surveys, and phone interviews. The primary outcome measure will be weight change from baseline. Secondary outcome measures will include percentage of patients eligible to undergo TJA, number of sessions completed with dietitians, self-reported global health status (PROMIS Global Health scale), self-reported joint-specific pain and function (Knee injury and Osteoarthritis Outcome Score (KOOS) or Hip disability and Osteoarthritis Outcome Score (HOOS)), and serologies such as hemoglobin A1c, total lymphocyte count, albumin, and transferrin. Qualitative responses transcribed from phone interviews about the intervention will also be analyzed. Discussion This will be the first study to assess pre-operative weight loss in patients with severe obesity anticipating orthopaedic surgery using an RD and mobile app intervention aimed at helping patients become eligible for TJA. Trial registration Registered on 1 April 2020 at Clincialtrials.gov. Trial number is NCT04330391 .